SCHOOL AS AN EFFECTIVE LEARNING ORGANIZATION - GAJDA, Joanna (Trends in education, 2012)
Working out a new educational paradigm is being forced in present times by a continuous transformation processes taking place in our modern world. A learning organization is currently considered to be a significant idea, showing new perspectives of self-improvement and development. A concept proposed by a P. Senge is a condition for an existence and development of school, engaged in a process of recognizing and understanding of complex and unpredictable situations.
Keywords: evolution; knowledge; creativity.